Confronting climate change : risks, implications, and responses - M Mintzer, Irving (Cambridge University, 2013)
The impact of potential climate change is a challenge to national and international planners and policy makers. Equally it challenges industry, commerce and all elements of the local or wider community. It is for these people that the book is written.